The process of globalization and cultural heritage issues (International relations and international law Journal, 2019)
The period of modern globalization is characterized by the interconnection of peoples and nations, as well as the expansion of cultural integration. The use of the scientific and technological progress acts as a major factor for the rapprochement of cultures and at the same time, creating common cultural values. Under such conditions, the existence of national cultural values feels threatened, and the long-standing cultural values have the possibility to change their essence. Many researchers believe that national cultural values can never be completely eliminated, even if they are exposed to the effects of modernization. However, historical experience proves that there are several national cultures which disappeared and many of them are exposed to assimilation. In this case, there is a need for the progressive increase of state intervention in the preservation of national cultures.Key words: globalization, global processes, cultural heritage, national and cultural values, intercultural dialogue